Rapid synthesis of hexahydropyrrolo[3, 4-b]pyrrole-fused quinolines via a consecutive [3 + 2] cycloaddition and reduction/intramolecular lactamization cascade. Issue 19 (11th September 2020) - Lin, Yan-Liang; Lee, Yun-Ta; Barve, Indrajeet J.; Huang, Yi-Ting; Sun, Chung-Ming
Abstract : An unprecedented synthesis of novel hexahydropyrrolo[3, 4- b ]pyrrole-fused quinolines is achieved through the sequential [3 + 2] cycloaddition reaction of azomethine ylides with maleimides followed by intramolecular lactamization. Abstract : An unprecedented synthesis of novel hexahydropyrrolo[3, 4- b ]pyrrole-fused quinolines is achieved through the sequential [3 + 2] cycloaddition reaction of azomethine ylides with maleimides followed by intramolecular lactamization. Condensation of the α-amino acid methyl ester with 2-nitrobenzaldehyde leads to an ester stabilized azomethine ylide which further reacts with maleimide to form hexahydropyrrolo[3, 4- c ]pyrrole. After the reduction of a nitro group, an unusual transamidation reaction is observed, furnishing the novel hexahydropyrrolo[3, 4- b ]pyrrole-fused quinolines. Isolation of the hexahydropyrrolo[3, 4- c ]pyrrole amide intermediate revealed the pathway of the reaction mechanism.